Cannabinoids and Pain for the Plastic Surgeon: What Is the Evidence?. (23rd June 2022) - Stephens, Kristen L.; Heineman, John T.; Forster, Grace L.; Timko, Michael P.; DeGeorge, Brent R.
Abstract : Background: Since the passage of the 2018 Farm Bill, practitioners have encountered more patients self-treating pain with over-the-counter topical cannabidiol (CBD) derived from hemp— Cannabis sativa with less than 0.3% delta-9-tetrahydrocannabinol—with reported improvements in pain control and activities of daily living. Cannabidiol has been touted for its capacity to improve inflammatory, arthritic, and neuropathic pain conditions, and increasing numbers of patients are exploring its use as potential replacement for opioids. However, limited rigorous clinical trials have been performed evaluating the safety and efficacy of cannabinoids for the treatment of pain. Methods: A systematic search of PubMed was performed using the Medical Subject Headings (MeSH) terms "cannabinoid" or "CBD" or "cannabidiol" or "cannabis" or "medical marijuana" and "pain." It yielded 340 article titles. Twelve full-text primary studies of oral or topical CBD for chronic pain were selected for review, including 6 animal (2 randomized clinical trial and 4 prospective trials) and 6 human (4 randomized clinical trial and 2 prospective trials) studies. Results: With respect to the safety and efficacy of oral and topical CBD for treating pain, animal and human studies have shown early positive results with limited minor side effects. However, all human studies may be underpowered with small sample sizes. Conclusions: With respect to the safety and efficacy of oral and topical CBD for treating pain, the evidence remains inconclusive in that we have a paucity of data to share with our patients who are considering the use of these products, which may be associated with significant costs.